Pengaruh Kekuatan Lengan, Kekuatan Tungkai dan Kelentukan Tubuh Terhadap Kemampuan Passing Bawah dalam Permainan Bolavoli pada Mahasiswa FIK UNM Makassar - Hikmad Hakim; Anto Sukamto; Addien Addien (Seminar Nasional LP2M UNM, 2019)
Abstract. This research aimed at finding out the effect of hand and leg strength and body flexibility toward lower pass ability in volley ball games. The population of research carried out at student of Faculty Sport science Maccasar Nation University. Sample are 30 person taken follow random sampling. Indepenent variable were hand and leg strength, Attribute variable was body flexibility, and Dependent variable of this research waslower pass ability at volley ball games.The research method is a descriptif. The data research was analysed with path analyses at significant level 95 %.The result of this research pointed that: 1) Hand strength was given direct effect that significance toward body flexibility at student of Faculty Sport science Maccasar Nation University ( ß = 0.399 with significant level 0.001 < α 0.05). 2) Leg strength was given direct effect that significance toward body flexibility at student of Faculty Sport science Maccasar Nation University. ( ß= 0.597 with significant level 0.011 < α 0.05). 3) Hand strength was given direct effect that significance toward lower pass ability in volley ball games at student of Faculty Sport science Maccasar Nation University ( ß = 0.279 with significant level 0.034< α 0.05). 4) Leg strength was given direct effect that significance toward lower pass ability in volley ball games at student of Faculty Sport science Maccasar Nation University ( ß = 0.301 with significant level 0.049< α 0.05). 5) Body flexibility was given direct effect that significance toward lower pass ability in volley ball games at student of Faculty Sport science Maccasar Nation University ( ß = 0.418 with significant level 0.030< α 0.05). 6) Hand strength was not given effect that significance toward lower pass ability in volley ball games through body flexibility at student of Faculty Sport science Maccasar Nation University ( ß = 0.167 <0.279). 7) Leg strength was not given effect that significance toward lower pass ability in volley ball games through body flexibility at student of Faculty Sport science Maccasar Nation University ( ß = 0.250 <0.301)Keywords: The Effect, Hand and Leg Strength, Body Flexibility, Lower pass, Volleyball